1988
DOI: 10.2134/jeq1988.00472425001700010022x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Transport through Selected Aquatic Macrophytes

Abstract: The extent of O2 transport from aerial plant tissue into the root zone was evaluated for several floating and emergent aquatic macrophytes that have characteristics favorable for wastewater treatment. The highest O2 transport rates from aerial tissue into the root zone were associated with plants having a small root mass. As root mass increased, the rate of O2 transport decreased for aquatic macrophytes evaluated. Pennywort (Hydrocotyle umbellata L.) had the highest O2 transport rate of all aquatic macrophytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 0 publications
2
32
0
2
Order By: Relevance
“…Sediment-dwelling benthic animals in turn can increase the percolation of water and oxygen levels through solute pumping or by the bioturbation associated with deposit-feeding or burrowing (Aller 1982;Rhoads and Boyer 1982). Vegetation has a similar effect by transporting oxygen to roots, where it enters the rhizosphere (Armstrong 1964; Moorhead and Reddy 1988). In addition, vegetation moderates rates of water flow, affecting animal movement, nutrient dynamics, and particle deposition (Jumars and Nowell 1984).…”
Section: Ctz Functionsmentioning
confidence: 99%
“…Sediment-dwelling benthic animals in turn can increase the percolation of water and oxygen levels through solute pumping or by the bioturbation associated with deposit-feeding or burrowing (Aller 1982;Rhoads and Boyer 1982). Vegetation has a similar effect by transporting oxygen to roots, where it enters the rhizosphere (Armstrong 1964; Moorhead and Reddy 1988). In addition, vegetation moderates rates of water flow, affecting animal movement, nutrient dynamics, and particle deposition (Jumars and Nowell 1984).…”
Section: Ctz Functionsmentioning
confidence: 99%
“…A study conducted by Moorhead and Reddy (1988) to evaluate oxygen transport into the root zone for several floating and emergent aquatic macrophytes showed that the highest transport rates were associated with plants having a small root mass. As root mass increased, the rate of oxygen transport decreased for the plants evaluated, suggesting that older plants and plants with extensive rooting systems probably consume more of the transported oxygen due to higher respiration rates.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…The concomitant higher O 2 uptake and the decrease in pH in these treatments also indicate the heterotrophic activity with CO 2 formation. Previous studies showed the capability of free-floating aquatic macrophytes in transporting oxygen from the foliage to the rhizosphere 45,46 . The roots within the water column act as a living substrate for the growth of attached aerobic bacteria, which consume the oxygen to decompose dissolved organic compounds 47 .…”
Section: Discussionmentioning
confidence: 99%